Implementation Of Pancasila Values in Teaching Learning Activities in Forming Multicultural Characters on Students - Endang Purwaningsih; Sulistyarini Sulistyarini; Raymond Kelvin Nando; Jagad Aditya Dewantara; Afandi Afandi (JED (Jurnal Etika Demokrasi), 2022)
The degradation of multicultural character in students is supported by concerns about this, the teacher as one of the things that must shape the character of students does not have basic values that must be used in the context of multicultural character in students. The purpose of this study is to re-analyze the values of Pancasila that can be used by teachers as a basis for forming multicultural characters in students. In this study used library research methods (Library Research). After analyzing several variables that become benchmarks in forming multicultural characters, among others: As a basis for social competence, social learning for the development of integrated intelligence, strengthening multicultural characters carried out in an institutionalized manner. This page is in English Translate to Indonesian    AfrikaansAlbanianAmharicArabicArmenianAzerbaijaniBengaliBulgarianCatalanCroatianCzechDanishDutchEnglishEstonianFinnishFrenchGermanGreekGujaratiHaitian CreoleHebrewHindiHungarianIcelandicIndonesianItalianJapaneseKannadaKazakhKhmerKoreanKurdish (Kurmanji)LaoLatvianLithuanianMalagasyMalayMalayalamMalteseMaoriMarathiMyanmar (Burmese)NepaliNorwegianPashtoPersianPolishPortuguesePunjabiRomanianRussianSamoanSimplified ChineseSlovakSlovenianSpanishSwedishTamilTeluguThaiTraditional ChineseTurkishUkrainianUrduVietnameseWelsh Always translate English to IndonesianPRO Never translate English Never translate journal.unismuh.ac.idTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//